Functional Characterization and Direct Comparison of Influenza A, B, C, and D NS1 Proteins in vitro and in vivo - Nogales, Aitor; Aydillo, Teresa; Ávila-Pérez, Gines; Escalera, Alba; Chiem, Kevin; Cadagan, Richard; DeDiego, Marta L.; Li, Feng; García-Sastre, Adolfo; Martínez-Sobrido, Luis (Frontiers in Microbiology, 2019)
Influenza viruses are important pathogens that affect multiple animal species, including humans. There are four types of influenza viruses: A, B, C, and D (IAV, IBV, ICV, and IDV, respectively). IAV and IBV are currently circulating in humans and are responsible of seasonal epidemics (IAV and IBV) and occasional pandemics (IAV). ICV is known to cause mild infections in humans and pigs, while the recently identified IDV primarily affect cattle and pigs. Influenza non-structural protein 1 (NS1) is a multifunctional protein encoded by the NS segment in all influenza types. The main function of NS1 is to counteract the host antiviral defense, including the production of interferon (IFN) and IFN-stimulated genes (ISGs), and therefore is considered an important viral pathogenic factor. Despite of homologous functions, the NS1 protein from the diverse influenza types share little amino acid sequence identity, suggesting possible differences in their mechanism(s) of action, interaction(s) with host factors, and contribution to viral replication and/or pathogenesis. In addition, although the NS1 protein of IAV, IBV and, to some extent ICV, have been previously studied, it is unclear if IDV NS1 has similar properties. Using an approach that allow us to express NS1 independently of the nuclear export protein from the viral NS segment, we have generated recombinant IAV expressing IAV, IBV, ICV, and IDV NS1 proteins. Although recombinant viruses expressing heterotypic (IBV, ICV, and IDV) NS1 proteins were able to replicate similarly in canine MDCK cells, their viral fitness was impaired in human A549 cells and they were highly attenuated in vivo. Our data suggest that despite the similarities to effectively counteract innate immune responses in vitro, the NS1 proteins of IBV, ICV, or IDV do not fully complement the functions of IAV NS1, resulting in deficient viral replication and pathogenesis in vivo.